The Role of Teacher Professionalism in Learning Differentiation of Independent Learning for Students - Somadayo, Samsu; Kurniawan, Heru (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
Professional teachers are teachers who can carry out learning activities well. One of them is implementing independent differentiation of learning in the classroom. For this reason, research was conducted to conceptualize the paradigm of learning differentiation in the context of realizing students’ independent learning. This study uses qualitative field research, examining data sources in books and journal articles discussing learning differentiation, teacher professionalism, and independent learning. The data collection technique used is documentation in the form of data sources from various reference sources, both journal articles, research results, and reference books. The analysis technique is carried out by reading, identifying, and classifying the data, which is then analyzed and criticized based on theoretical concepts. This is where the findings in this study can be identified as follows: (1) the teacher must have a paradigm view that independent learning differentiation already exists in the classroom. The classroom is positioned as a space for the diversity and diversity of students. This difference is a privilege that must be explored in independent learning activities; (2) professional teachers can develop differentiation designs for students’ independent learning. Learning differentiation can be contextualized in the independent learning paradigm; and (3) teachers can implement independent differentiation of learning in the classroom through a series of activities: constructivism, inquiry, asking, study groups, modeling, reflection, and authentic assessment.